2013
DOI: 10.1523/jneurosci.1552-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of Baclofen on Use-Dependent Modulation of GABAB Inhibition after Tetraplegia

Abstract: Baclofen is a GABA B receptor agonist commonly used to relief spasticity related to motor disorders. The effects of baclofen on voluntary motor output are limited and not yet understood. Using noninvasive transcranial magnetic and electrical stimulation techniques, we examined electrophysiological measures probably involving GABA B (long-interval intracortical inhibition and the cortical silent period) and GABA A (short-interval intracortical inhibition) receptors, which are inhibitory effects mediated by subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 68 publications
(16 reference statements)
8
44
2
Order By: Relevance
“…Single unit recordings in primates showed that spinal interneurons exert postspike effects in hand muscles during a precision grip (Takei and Seki, 2010) in a task-dependent manner (Takei and Seki, 2013). Although lesions of the corticospinal tract at the cervical spinal cord level showed in most cases recovery of the ability to grasp with the index finger and thumb (Sasaki et al, 2004;Alstermark et al, 2011;Hoogewoud et al, 2013), likely related to time-dependent central compensatory mechanisms underlying the recovery of finger dexterity (Nishimura et al, , 2009Isa et al, 2013), the contribution of subcortical pathways to the control of precision grip in humans with subcortical damage due to incomplete spinal cord injury (SCI) remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Single unit recordings in primates showed that spinal interneurons exert postspike effects in hand muscles during a precision grip (Takei and Seki, 2010) in a task-dependent manner (Takei and Seki, 2013). Although lesions of the corticospinal tract at the cervical spinal cord level showed in most cases recovery of the ability to grasp with the index finger and thumb (Sasaki et al, 2004;Alstermark et al, 2011;Hoogewoud et al, 2013), likely related to time-dependent central compensatory mechanisms underlying the recovery of finger dexterity (Nishimura et al, , 2009Isa et al, 2013), the contribution of subcortical pathways to the control of precision grip in humans with subcortical damage due to incomplete spinal cord injury (SCI) remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the SP during 25% of MVC increased in SCI groups irrespective of baclofen use compared with uninjured participants [51]. There was also no difference in the cSP between SCI participants who were or were not taking baclofen.…”
Section: Intra Cortical Facilitation (Icf) Involves a Sub Threshold Omentioning
confidence: 78%
“…These data indicate that baclofen creates typical modulation of LICI circuitry in the SCI population and that baclofen appears to normalize LICI function following SCI. The limited amount of research done regarding the LICI circuit within the SCI population shows an increase in the GABA B mediated circuit compared to uninjured, however the presence of baclofen appears to alter function of this circuit to similar levels of uninjured [51] LICI holds much of the same methodological limitations as SICI due to the similarities in the way they are both elicited. Therefore, changes to the motor threshold and MEP amplitude can affect LICI data interpretation in SCI.…”
Section: Short Interval Intra Cortical Inhibition (Sici)mentioning
confidence: 99%
See 1 more Smart Citation
“…Baclofen is one such agonist that reduces the magnitude of SICI via presynaptic inhibition of GABAA neuron populations by GABAB receptors [3,13,14] . This medication is commonly prescribed to patients following SCI to reduce spasticity.…”
Section: Alterations To Intracortical Inhibitory Action Following Spimentioning
confidence: 99%